Development and implementation of an expert system for insect-pests management in pulses - DEVRAJ, DEVRAJ; JAIN, RENU; DEEP, VIKAS; MISHRA, SAKET (The Indian Journal of Agricultural Sciences, 2018)
The paper describes the development and implementation of an expert system for the management of insect-pests in pulse crops. System facilitates â€œfarmers/extension workersâ€ in diagnosing insect-pests of major pulse crops, viz. chickpea, pigeonpea, mungbean and urdbean (highly consumed pulse crops) and suggests the appropriate control measures. Knowledge acquisition system provides online interface to the domain experts for entering, storing and structuring the domain specific knowledge. The system holds an integrated knowledge base containing information for the diagnosing of 20 major insect-pests of pulses appearing right from seedling to maturity stage. The system provides user-friendly interface to users and asks the textual as well as pictographic symptoms in the form of multiplechoice questions. On the basis of answers, system diagnosis the pulse crop insect-pests along with its confidencefactor and suggests most appropriate treatments. The systemâ€™s performance was found good and comparison between recommendations of human experts and system itself showed 92% agreement.